2015
DOI: 10.1002/jrs.4718
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin adsorbed onto magnetite nanoparticle: SERS study and insight on the molecular arrangement and light effect

Abstract: In this study, the surface-enhanced Raman spectroscopy (SERS) technique was used to asses key information regarding the surface adsorption of Rifampicin (RIF) onto magnetite nanoparticle previously dressed with a bilayer of lauric acid (LA). The effects of white light illumination on the physicochemical properties of the RIF molecule were also investigated. Transmission electron microscopy, dynamic light scattering, zeta-potential, and Fourier transform infrared spectroscopy were also employed to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The results suggested that the species binding to the outer carboxylate group of the LA‐bilayer is more likely than the piperazine nitrogen adjacent to the imine nitrogen. The SERS data also revealed the enhancement of RIF molecular stability to white light irradiation while adsorbed onto the magnetite nanoparticle . Li et al .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 91%
“…The results suggested that the species binding to the outer carboxylate group of the LA‐bilayer is more likely than the piperazine nitrogen adjacent to the imine nitrogen. The SERS data also revealed the enhancement of RIF molecular stability to white light irradiation while adsorbed onto the magnetite nanoparticle . Li et al .…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 91%
“…It is noteworthy that RP has several moieties which could be anchor sites for the adsorption. Silver colloids based on reduction by hydroxylamine led to different spectral patterns with different pH conditions [22], while the interactions of RP with lauric acid bilayer in the presence of DMSO showed particular features, probably due to the differences in the chemical environment [23].…”
Section: Fig 1 Presents the Analysis Of Rp Interactions With Agnp Andmentioning
confidence: 99%
“…The authors showed that the spectral pattern of adsorbed RP changes with protonation condition, being very similar to the RR spectrum at lower pH. The SERS spectra of RP on silver surfaces, involving interactions with lauric acid, DMSO and magnetite nanoparticles were reported [23], and the vibrational assignment allowed to infer RP adsorbs without interactions with the surface of SERS substrate.…”
Section: Introductionmentioning
confidence: 96%
“…The solid, black-colored sample resulting from this step was decanted under a neodymium magnet and the supernatant was removed. The pellet was functionalized by adding 2.0 g of lauric acid (AL) (Sigma-Aldrich) under mechanical stirring and heating (90 °C) for 20 minutes (Van Ewijk et al 1999;Ferreira et al 2015). The magnetic fluid resulting from this step was taken for oxidation of the particles via bubbled oxygen under heating (90 °C) for a period of 8 h (Kang et al 1996).…”
Section: Synthesismentioning
confidence: 99%
“…Afterward, it was submitted to magnetic separation with a neodymium magnet (400 Gauss) for 48 h under refrigeration (2 °C) and protected from light. The supernatant liquid resulting from this separation was used for quantification of free RIF, i.e., not incorporated into the nanosystem (Ferreira et al 2015).…”
Section: Synthesismentioning
confidence: 99%